The Extent of Adoption the Principles University's Total Quality Management in Algerian Universities - Ali Mekkid; Lakhdar Meddah (University of Science and Technology, Yemen, 2015)
The aim of This Study is to show the conceptual framework of the total quality management in general, and in the university in particular .This being by the most important principles of university's total quality management, right down to test the extent of adoption of the most important principles of total quality management in the university under study. The study was confined to an Algerian institution of higher education, representing by the faculty of economic, commercial and management sciences, Medea University- Algeria, the population of the study represent by faculty's permanent members, the research sample has been chosen randomly, composed of 80 members, who represent 30.65% percent from the whole study population, we used the questionnaire as astudytool, which helped us to collect data to measure the extent of adoption the principles university's total quality management in the faculty, also we used the analysis of the data on the statistical methods available in the program statistical package for social sciences (SPSS), arithmetic means and standard deviations, so as to know the extent of deviation responses of the sample for each of the phrases of the total quality management principles, relating to the second axe of study, as well as the total deviation of the overall average for each principle from the principles that have been addressed. Among the most important results that members agree on the fact that the features of the principles university's total quality management adopted by faculty of economic, commercial and management sciences, Medea, the Algerian University, and this was confirmed by the overall average of circulated principles, where the overall average for the principles (3.25 of 5), by standard deviation of 1.05, which is an average under the fourth category of the Fifth Likert Scale categories (from 3.41 to 4.20) a category that refers to the response "agree".